Quantitative flow ratio for the functional assessment of extracranial internal carotid artery stenosis. (14th October 2021) - Franzese, M; Di Serafino, L; Stabile, E; Giugliano, G; Leone, A; Ilardi, F; Strisciuglio, T; Esposito, G
Abstract: Background: In asymptomatic patients at high surgical risk presenting with significant extracranial internal carotid artery stenoses, a selective invasive angiography is performed before carotid artery stenting (CAS). Sometimes, the angiographic findings of the stenosis could be discordant from those observed at the non-invasive imaging evaluation and the use of a pressure-wire to evaluate the hemodynamic potential of the stenosis, might be dangerous for the higher risk of cerebrovascular events. Purpose: The Quantitative Flow Ratio (QFR), by estimating the contrast flow velocity and based on a 3-dimensional quantitative angiography, might be of value as an online angiography-based functional assessment of internal carotid stenoses, in order to guide the physicians in the decision-making process to proceed or not to revascularization. Methods: We prospectively enrolled 14 asymptomatic patients with an indication for invasive treatment of internal carotid artery stenosis. The echo-colour-Doppler was performed in 28 vessels and the Peak Systolic Velocity (PSV, cm/sec) was used to identify functionally significant stenoses (PSV >120cm/sec). At the angiography, internal carotid artery stenosis degree was obtained according to NASCET criteria (%DSNASCET) and the lesion considered angiographically significant if >60%. After the exclusion of 4 vessels, QFR, Area Stenosis (AS, %) and Minimal Lumen Area (MLA, mm 2 ) were obtained in the remaining 24 vessels (Figure 1, Panel A and B). Results: At the linear regression analysis, QFR values significantly correlated with PSV (r2=0.71, p<0.001) as well as with %DSNASCET (r2=0.81, p<0.001). In addition, using the PSV as reference, QFR showed good accuracy to predict the presence of a functionally significant stenosis (AUC=1.00, p<0.001) with a cut-off value of 0.90. Similarly, the MLA significantly correlated with both the PSV and %DSNASCET (respectively, r2=0.61 and r2=0.60, p<0.001) as well as the AS (respectively, r2=0.68 and r2=0.87, p<0.001) (Figure 2). Conclusion: This study suggests the possibility to adopt QFR for the functional assessment of extracranial internal carotid artery stenoses and should be considered as hypothesis generating to design a larger validation trial. Funding Acknowledgement: Type of funding sources: None.